A training needs analysis and a proposed training program for the non-teaching staff of a college in Metro Manila - Burgos, B'julah Silva (Animo Repository, 1994)
This study seeks to determine the extent of the training needs of the non-teaching staff of a College in Metro Manila as perceived by themselves and their supervisors in terms of the cognitive interpersonal and psychomotor skills in order to propose a training program based on the most prevalent needs. This study employed the descriptive method using the techniques of interview, questionnaire and content analysis of existing data. The respondents of this study were 91 non-teaching staff from the clerical, manual, and technical workers and 29 supervisors. A questionnaire containing the different training areas was used to assess the extent of the training needs of the subjects. The mean was employed to determine the extent of training needs while the t-test was used in measuring the difference in perceptions of the respondents. Results of the study showed that the non-teaching staff need training in most areas of skills required of them. It was also revealed that there was a highly significant difference in the perceptions of the non-teaching staff and their supervisors as to the extent of training needs of the staff.